Toy story 2 [in 3D] - Lasseter, John; Hanks, Tom; Allen, Tim, 1953-; Cusack, Joan, 1962-; Rickles, Don; Varney, Jim; Shawn, Wallace; Ratzenberger, John; Potts, Annie; Knight, Wayne (Walt Disney Studios Home Entertainment, 2011)
The fun and adventure continues when Andy goes off to cowboy camp and the toys are left to their own devices. Things shift into high gear when an obsessive toy collector kidnaps Woody, who hasn't the slightest clue that he's a greatly valued collectible.